Avaliação da atividade fotoprotetora in vitro de extratos etanólicos de três espécies de Marcetia e suas formulações - Costa, Sônia Carine Cova (2015)
Solar radiation is the main factor in the appearance of skin diseases. Preventive measures against skin photoaging are necessary and one of the ways to avoid it is to use sunscreen. The genus Marcetia (Melastomataceae) is endemic of rocky fields in northeastern Brazil and are adapted to high sunlight conditions due to bioproduction of flavonoids. The initial goal of this work was to evaluate the antioxidant activities, photoprotection (UVB/UVA) and toxicity of ethanolic extracts of M. taxifolia, M. macrophylla and M. latifolia. Thus, it was investigated the potential photoprotection of the extracts incorporated at 5, 10, 20 and 30% by polawax® lotion. All tests were performed in vitro. The formulations were evaluated in the physicochemical standpoint. In addition it was held HPLC-DAD for identification and quantification of flavonoids. The spectrophotometric method was used to determine the total level of flavonoids (TFC), DPPH• (antioxidant activity) and photoprotective activity (UVB/UVA). The evaluation of toxicity was made by means of the HET-CAM test, and hemolysis rate. The most promising extract was fractionated. Photoprotective formulations have been developed (5, 10, 20 and 30%), which also had their sunscreen profile UVB / UVA evaluated. The M. taxifolia showed higher quercetin content, with 55.78 g/Kg and 168 g/mL, following the studies of HPLC-DAD and TFT. All Marcetia ssp extracts had an antioxidant activity around 95%. Likewise, the three species had good results to SPF and UVA photoprotection. The species that has better value SPF was M. macrophylla (20.25) and UVA protection was M. taxifolia (86.04%), but these species have a higher toxic potential related to M. latifolia, which also had a good value SPF (13.12) and UVA (78.09%). The toxicity results show that this species is more secure and is considered an irritant and of weak hemolysis rate (23.51%), while the other species had a hemolysis rate  50%. Given these results EEML was fractionated into five fractions (MLFR02, MLFR03, MLFR04, MLFR05, MLFR06). After testing, MLFR02 showed good UVB sunscreen activity (17,52) and UVA (87.49%), but the safest was MLFR02 beyond presenting results in a high SPF value (37.82) when incorporated into the emulsion which makes it suitable for individuals who are very sensitive to sunburn.